Pengembangan Aplikasi Pencatatan Penilaian Anak bagi Guru PAUD - Ana Falera (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
The focus of this research is the Child Assessment Recording Application which was created to facilitate Early Childhood educators in recording children's assessments and also assessments in daily, daily, monthly and semester assessments. This research is a development research called research and development (RnD) using the Borg and Gall model. This research procedure uses ten steps, starting from research testing and initial information collection, application planning, development of an initialapplication form, initial field trial, initial field trial revision, main field trial, main field test revision, implementation trial, application improvement. and finally the deployment of the application. The application was piloted on AUD educators through three stages, namely initial field trials, main field trials, and implementation trials. Eligibility of application based on the results of materials experts, design experts and AUD educators. Data collection techniques in this study using questionnaires, observation and interviews. Descriptive data analysis in the form of quantitative and qualitative. Based on the results of material expert validation with an average value of 4.25, it is included in the appropriate category, design experts with an average value of 4.42 are included in the appropriate category, and implementation trials with an average value of 93.3% are included in the feasible category. Based on the results of the research conducted, it can be concluded that APPA is feasible to use.